Influence of surface imperfections caused by thruster elements on the aerodynamics of a supersonic projectile. (1st January 2014) - Hruschka, R.; Klatt, D.; Leopold, F.
Pulsed side jet thrusters can be used to correct the trajectory of supersonic projectiles. After their time-of-action, these pyrotechnical thrusters leave a hole in the shaft, which sometimes also features a protuberance or burr at its rim. The current work quantifies the aerodynamic interference caused by this sub-boundary-layer disturbance by means of 3-axis-force balance measurements in a supersonic wind tunnel at Mach 3 at angles of attack between 0 and 10 degrees. Supplementary numerical time- and scale-resolving detached eddy simulations (DES) of the wind tunnel setup as well as basic theoretical correlations also support the experimental result that aerodynamic coefficients change by less than 2%, if the hole diameter is in the order of half a calibre and surface deformations protrude less than 2.5% of the calibre.